2021
DOI: 10.3390/geosciences11090379
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity Patterns Prior to the Thessaly (Mw6.3) Strong Earthquake on 3 March 2021 in Terms of Multiresolution Wavelets and Natural Time Analysis

Abstract: On 3 March 2021, a strong, shallow earthquake of moment magnitude, Mw6.3, occurred in northern Thessaly (Central Greece). To investigate possible complex correlations in the evolution of seismicity in the broader area of Central Greece before the Mw6.3 event, we apply the methods of multiresolution wavelet analysis (MRWA) and natural time (NT) analysis. The description of seismicity evolution by critical parameters defined by NT analysis, integrated with the results of MRWA as the initiation point for the NT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
(83 reference statements)
6
11
0
Order By: Relevance
“…The proper interpretation of the data acquired by these sensing techniques, in the direction of revealing hidden pre-failure indicators, is among the challenges of the current scientific research [8,9]. Various approaches have been proposed to analyze the experimental data, such as the b-value analysis [10,11], models based on wavelets [12,13] and natural time (NT) [14,15], analyses based on non-extensive statistical physics (NESP) [16,17], power-law models [18,19] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The proper interpretation of the data acquired by these sensing techniques, in the direction of revealing hidden pre-failure indicators, is among the challenges of the current scientific research [8,9]. Various approaches have been proposed to analyze the experimental data, such as the b-value analysis [10,11], models based on wavelets [12,13] and natural time (NT) [14,15], analyses based on non-extensive statistical physics (NESP) [16,17], power-law models [18,19] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Natural time was introduced [ 5 ] in 2001 as a general method to analyze time-series resulting from complex systems [ 7 ]. It has been applied to a variety of fields, such as condensed matter physics [ 22 , 23 , 24 ], geophysics [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], civil engineering [ 35 , 36 , 37 , 38 ], climatology [ 39 , 40 , 41 , 42 ], and biomedical engineering [ 43 , 44 ]. Within the concept of NTA, it has been shown that the variance of natural time may be considered as an order parameter for seismicity [ 3 , 45 , 46 , 47 , 48 , 49 ] as well as in acoustic emission before fracture [ 28 , 50 ] or in other self-organized critical phenomena such as ricepiles [ 51 ] and avalanches in the Olami–Feder–Christensen [ 52 ] earthquake model [ 53 ] or in the Burridge–Knopoff [ 54 ] train model [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are other studies that focus on the aspect that earthquakes are critical phenomena. For example, regarding earthquake occurrence as point process, small earthquakes before large earthquakes were analyzed by the means of multiresolution wavelet analysis and natural time analysis [22]. It is proposed that we could know whether the crustal state is at a critical stage of earthquake occurrence by extracting critical parameters.…”
Section: Discussionmentioning
confidence: 99%